Menggugah Sensitivitas Sosial Mahasiswa Melalui Implementasi Praksis Sosial - Wahyu Djoko Sulistyo (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2019)
One problem that is a common challenge for students today is the low level of social sensitivity they have. Though this is one of the character values that they should have as agents of changing times. Being indifferent and busy with his own activities is one of the characteristics of this millennial generation. In this paper describes the implementation of social praxis activities that become compulsory subjects for UM FIS students. Through various activities that they have planned and carried out in the field with a direct target to the community, they are able to have a significant influence in developing social sensitivity. The implementation is able to provide direct experience for students to engage directly and intersect with the community.